1999
DOI: 10.1128/jb.181.9.2852-2862.1999
|View full text |Cite
|
Sign up to set email alerts
|

YscP of Yersinia pestis Is a Secreted Component of the Yop Secretion System

Abstract: The Yersinia pestis low-Ca2+ response stimulon is responsible for the environmentally regulated expression and secretion of antihost proteins (V antigen and Yops). We have previously shown that yscO encodes a secreted core component of the Yop secretion (Ysc) mechanism. In this study, we constructed and characterized in-frame deletions in the adjacent gene,yscP, in the yscN–yscU operon. The ΔP1 mutation, which removed amino acids 246 to 333 of YscP, had no effect on Yop expression or secretion, and the mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 54 publications
2
30
1
Order By: Relevance
“…For this study, we cloned yscP ent and we engineered a larger deletion, removing residues 97±465 in Y. enterocolitica MRS40. At first sight, our results were different from those of Payne and Straley (1999).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For this study, we cloned yscP ent and we engineered a larger deletion, removing residues 97±465 in Y. enterocolitica MRS40. At first sight, our results were different from those of Payne and Straley (1999).…”
Section: Discussioncontrasting
confidence: 99%
“…However, this product of about 20 kDa partially restored Yop secretion at 378C in the absence of Ca 21 ions. This result showed that YscP D572324 is partially functional, which explains the leaky phenotype described by Payne and Straley (1999). In conclusion, our results demonstrate that YscP is absolutely required for Yop secretion but that, surprisingly, a severely truncated protein, missing 267 central residues, still has some activity.…”
Section: Yscp Is Absolutely Required For In Vitro Yop Secretionmentioning
confidence: 52%
See 1 more Smart Citation
“…Two ring structures, one in the bacterial plasma membrane and one in the outer membrane, are joined via a central rod that is formed from YscI, which is also thought to connect with the needle protein at the level of the outer YscC ring (Marlovits et al, 2004;Marlovits et al, 2006). Needle polymerization is controlled by YscP, a secreted machine component (Payne and Straley, 1999;Journet et al, 2003). Without yscP, Yersinia polymerize extended needles and are unable to inject effectors into host cells .…”
Section: Introductionmentioning
confidence: 99%
“…What might be different about blocking substrates and non-blocking substrates, which can be rejected from the type III pathway? YopR and YscP do not share obvious physical features, though they do have a few functional attributes in common: neither YopR nor YscP is injected into eukaryotic cells and neither is thought to possess a chaperone (Lee et al, 1998;Payne and Straley, 1999). Both are phenotypically or genetically linked to the formation of the needle filament: yopR is immediately flanked by genes that encode the building blocks for the needle filament though the contribution of YopR to this process is unclear (Allaoui et al, 1995).…”
Section: Introductionmentioning
confidence: 99%